ANALISIS PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN KSP PURNA YUDHA KABUPATEN MAGELANG - Vina Rosalinda; Rima Parawati Bala (Riset Manajemen dan Akuntansi, 2023)
The purpose of this study is to examine the influence of motivation and leadership style on the performance of KSP Purna Yudha employees of Magelang Regency. The population as well as the sample in this study are all employees at KSP Purna Yudha Magelang Regency with a total of 40 employees.  Data collection techniques were used in this study through the distribution of questionnaires. The data analysis methods used include analysis of research instruments consisting of validity tests, reliability tests, classical assumption tests, and hypothesis tests.Result.. The results of this study show that motivation partially has a positive and significant effect on Employee Performance, leadership style has a positive and significant effect on Employee Performance. Simultaneously, the results of motivation and leadership style were obtained to have a positive and significant effect on the Performance of KSP Purna Yudha Employees of Magelang Regency.The results of this study also show that the motivation variable is the most dominant variable in influencing the Performance of KSP Purna Yudha Employees in Magelang Regency.